Efficacy of neem leaf, nishyinda leaf and turmeric rhizome supplementation on the growth performance of broiler chicken - Sultana, Nahid Nawrin; Mou, Soheli Jahan; Mostofa, Mahbub; Rahman, Md Abdur (Research in Agriculture Livestock and Fisheries, 2016)
This experiment was conducted to evaluate the efficacy of Neem (Azadirachta indica) leaf, Nishyinda (Vitex nogundo) leaf and Turmeric rhizome (Curcuma longa) powdered supplementation in drinking water as a growth promoter in broiler chickens. A total of 40 day-old Cobb 40 broiler chicks were purchased from local hatchery (Nourish Poultry & Hatchery Ltd.) and after seven days of acclimatization chicks were randomly divided into two groups, A and B. The group A was kept as a control and not treated. The group B was supplemented with Neem, Nishyinda leaves and Turmeric dried powder with feed and water. Weekly observations were recorded for live body weight gain up to 5th weeks and hematological tests were performed at 7th and 35th days age of broiler to search for hematological change between control (A) and treatment (B) groups. The initial body weight of groups A and B on 7th day of this experiment were 130±4.35 gm, respectively and after 35th day of experiment final body weight were 150±47.35 gm and 1600±58.56 gm, respectively; the net body weight gain were 1320±43.79 gm and 1470±54.25 gm, respectively and economics of production were analyzed and found that net profit per broiler was Tk. 17.24 and Tk. 30.00, respectively. The treatment group B was recorded statistically significant (at 1% level) increase for live body weight than that of control group A. The hematological difference, while Hb. estimation does not show significant difference from control group. The results suggest that better growth performance could be achieved in broilers supplemented with Neem, Nishyinda leaves and Turmeric rhizome extract. Res. Agric., Livest. Fish.3(2): 331-338, August 2016